Analisis Kinerja dan Dampak Variabel Determinan Terhadap Minat Kerja dan Kesiapan Kerja - Julius Nursyamsi; Edi Sukirman; Joko Utomo; Makmun Makmun (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effects of self-efficacy, self-esteem, and soft skills on job interest and work readiness, as well as to examine the mediating role of job interest in the relationship between these three determinant variables and work readiness. The study employed a quantitative approach. The research population consisted of 500 individuals who met the predetermined research criteria, while the sample comprised 200 respondents, selected using a non-probability sampling technique with a purposive sampling method. Primary data were collected through a structured questionnaire measured using a five-point Likert scale. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The analytical procedures included the evaluation of the measurement model (outer model), structural model (inner model), hypothesis testing through bootstrapping, as well as predictive relevance (Q²), effect size (f²), and coefficient of determination (R²) analyses. The findings indicate that self-efficacy, self-esteem, and soft skills have positive and significant effects on both job interest and work readiness. Among these variables, soft skills exert the strongest influence on both job interest and work readiness. Furthermore, job interest has a positive and significant effect on work readiness and partially mediates the relationships between self-efficacy, self-esteem, soft skills, and work readiness. The Q² and R² values demonstrate that the proposed model possesses strong predictive capability in explaining the relationships among the variables. These findings reinforce the Social Cognitive Career Theory (SCCT) and the CareerEDGE Employability Model, emphasizing that work readiness is developed through the interaction of psychological factors, non-technical competencies, and career motivation. This study contributes theoretically by extending empirical evidence regarding the mediating role of job interest in the development of work readiness and contributes practically by providing insights for higher education institutions, vocational education providers, and organizations in designing programs that enhance self-efficacy, self-esteem, and particularly soft skills to improve graduates' work readiness in response to the demands of the digital transformation era.